Contribution of Factor VIII A2 Domain Residues 400–409 to a Factor X-Interactive Site in the Factor Xase Complex - Takeyama, Masahiro; Nogami, Keiji; Sasai, Kana; Furukawa, Shoko; Shima, Midori (Thrombosis and Haemostasis, 2018)
The link between factor (F)VIII and FX is essential for optimum activity of the tenase complex. The interactive site(s) in FVIII for FX remains to be completely clarified, however. We investigated the FVIII A2 domain-FX association that was speculated from inhibitory mechanism(s) by an anti-A2 autoantibody. SDS-PAGE demonstrated that the purified inhibitor IgG recognizing residues 373–562 blocked FXa cleavage at Arg372 in FVIII, and surface-plasmon resonance (SPR)-based assays showed that intact A2 subunit directly bound to FX (Kd; 63 nM). The FVIII structure model indicated possible FX-binding site(s) in residues 400–429 in A2. One peptide corresponding to residues 400–409 competitively inhibited both the A2–FX binding and FVIIIa/FIXa-dependent FXa generation. Covalent cross-linking was observed between this peptide and FX following reaction with EDC (1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide) using SDS-PAGE. K408 and S409 were not evident in N-terminal sequence analysis of the cross-linked product, suggesting that two residues participated in cross-link formation. SPR-based assays using recombinant FVIII mutants with one or both residues substituted to alanine demonstrated that K408A and K408A/S409A had approximately fourfold high Kd values of wild-type (WT-)FVIII. FXa cleavages at Arg372 in both mutants were significantly delayed, suggesting a contribution of K408 for FXa cleavage at Arg372. Furthermore, FXa generation assays with these mutants demonstrated that the Km values were 1.4- to 1.7-fold greater, and overall catalytic efficiency (kcat/Km) was 0.49- to 0.89-fold lower than with WT-FVIII, suggesting a significant contribution of K408 for FVIII–FX interaction in tenase assembly. We concluded that the K408 in the A2 domain provided an interactive-site for FX.
Keywords: factor VIII; A2 domain; factor X; binding site; tenase complex